Prognosis impact of ticagrelor vs clopidogrel based DAPT discontinuation after acute coronary syndrome. Insights from the multicenter CREA ARIAM Andalucia registry. (2nd May 2022) - Hernandez Meneses, BG; Padilla-Rodriguez, G; Carmona-Carmona, J; Hidalgo-Urbano, R; Almendro-Delia, M; Garcia-Rubira, JC
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): The study project was financially supported by a non-conditional grant by Astrazeneca. Background/Introduction: Premature cessation of dual antiplatelet therapy (DAPT) after acute coronary syndrome (ACS) has been associated with increased risk of major adverse cardiovascular events (MACE) Purpose: To assess the relationship between premature DAPT discontinuation versus therapy continuation and outcomes in ACS patients discharged on ticagrelor or clopidogrel. Methods: Prospective, observational, multicentre all-comers registry of ACS patients who were intended to receive 12-month DAPT with ticagrelor or clopidogrel. Adherence was defined by the medication possession ratio metric (MPA, proportion of days of medication supply within a time interval). Categories for DAPT cessation included: physician-recommended discontinuation, brief interruption (invasive procedures), or disruption due to non-compliance or because of bleeding. Fully-adjusted Cox models with time-varying covariates to account for informative censoring, were used to examine the effect of DAPT cessation on MACE (a composite of all-cause death, non-fatal myocardial infarction, non-fatal stroke, definite stent thrombosis, or target-lesion revascularization). Moderation analysis was also performed to assess for potential exposure-adherence interaction. Results: Among 2070 patients included (mean age 63 years, 73% men), 150 (7.3%) prematurely discontinued DAPT, median (IQR) 214 (101-236) days. Significantly more clopidogrel than ticagrelor users discontinued medication (9.5% vs 5%, respectively; P = .001), though timing of cessation was similar in both groups. At 1 year, MPR was slightly higher, but not significantly different, in the clopidogrel group than in the ticagrelor group (70±30 vs 64±29; P = .06). Overall, physician-guided discontinuation and bleeding were the main reasons for DAPT cessation. These were observed with a similar rate in both groups, while non-compliant disruption was more common among ticagrelor- than clopidogrel-treated patients (8% vs 2%, respectively; P for trend .04). After adjustments, DAPT cessation was associated with significantly increased risk of MACE (adjusted HR 2.94; 95% CI 1.82 – 4.74; P < .0001), regardless of the P2Y12 inhibitor (P interaction = 0.665). Non-compliance related cessation resulted in higher risk of MACE (HR 6.04, 95%CI 2.15 – 16.95; P = .001). Conclusion(s): Overall, approximately 7% of patients discontinued DAPT. Early cessation of either ticagrelor- or clopidogrel-based DAPT portended to a near 3-fold increased risk of MACE. Disruption due to non-compliance resulted in higher risk for ischemic events. These data warrant efforts to focus on patient education in subgroups at high risk of non-compliance.